Pengembangan Mobile-Learning SARITHA-Apps Untuk Meningkatkan Hasil Belajar Dan Berpikir Kritis Mahasiswa S1 Pendidikan Biologi Universitas Palangka Raya - Elda Susanti E. B. Dopo; Agus Haryono; Saritha Kittie Uda; Aditama Kittie Aidon Uda (Jurnal Ilmiah Kanderang Tingang, 2024)
This research aims to develop mobile-learning SARITHA-Apps, describe product validity, analyze the development of mobile-learning SARITHA-Apps towards improving learning outcomes and critical thinking of undergraduate students in the Biology Education Study Program, FKIP Palangka Raya University. This research refers to the ADDIE development design and data collection using questionnaire sheets, media expert assessment sheets and material expert assessment sheets. The research results show: (1) one product has been produced as a result of the development of Mobile-Learning Environmental Science material, namely the SARITHA-Apps Mobile-Learning Application; (2) The average result of the Expert Team's assessment of the suitability of the SARITHA-Apps Mobile-Learning Application instrument and product is 91%, which means it is in the "Very Feasible" qualification; (2) The SARITHA-Apps Mobile-Learning application is able to improve student learning outcomes for environmental science material, namely with an N-Gain of 0.4, which means it is in the "Medium" category; (3) Student learning outcomes according to critical thinking skills from the questions given, it was found that the explanation indicator had the highest percentage increase value, namely 6% compared to the percentage increase in other critical thinking indicators, where the self-regulation indicator was 5%, while the analysis and analysis indicators inference of 2%.